AN ANALYSIS OF FEMINISM AND CLASS INEQUALITY: A CASE STUDY OF KATNISS EVERDEEN IN THE HUNGER GAMES - Boonyaruksa, Sarawut (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
The present study aims to investigate the feminist representation of Katniss Everdeen. The development of Katniss’ feminist characteristics from the beginning to the end of the movie and class inequality in the novel. For this reason, The Hunger Games was used as the main data source for yielding research findings. The study is viewed under Marxist feminism. This study is qualitative research. Close reading techniques were employed to extract related quotes. The critical lens of literary works was used as the analysis tool in the present study. The findings revealed that Marxist feminism confirmed that Katniss must survive because she is the only leader of her family after her father’s death. Katniss is the protagonist and narrator of the novel. She is a strong, practical sixteen-year-old girl who is far more mature than her real age. Her character does not change from the beginning, but after meeting Peeta, she develops her love for Peeta. There are differences between the rich and the poor in terms of class inequality. Rich people have a better life than the poor. The fight against class inequality in the novel showed that there is a powerful character in Katniss who has a strong desire to change the nation. She takes down the Capitol and destroys the dictatorship. Finally, real democracy has arrived. Class inequality was destroyed. People live happily in this nation.